(untitled) - Reimold, Cheryl (Hoboken, N.J., 2003)
Speakers bear the responsibility for communicating effectively with their audience: presenting a clear message, supporting it with well-structured explanations and examples, and delivering it with ease, grace, and good visuals. Unfortunately, this rarely happens, as anyone who has endured a substandard presentation knows only too well. The key for developing sound presentation skills need not, however, remain hidden. The Short Road to Great Presentations demystifies the art of public speaking as it shows you how to master the critical principles to make this skill an invaluable asset of your life and career. Drawing on twenty years of experience in helping engineers, scientists, and business people develop powerful communication skills, PERC Communications founders Peter and Cheryl Reimold present an easy-to-follow program for crafting winning presentations. They focus on two principles: 1) find a message that is clearly meaningful and accessible to your audience, and 2) connect strongly with your audience throughout your presentation. In applying these principles to a series of step-by-step preparations and on-stage actions, the authors help speakers focus on their most vital content, strengthen their structure and delivery, and???perhaps, most important???eliminate stress and aggravation. Chapter topics in this reader-friendly guide include: Structuring your message for maximum effect. Preparing effective visuals
Keywords: Business presentations,Thuyết trình kinh doanh